Evaluation of Social Media Use by Emergency Medicine Residents and Faculty - Patterson, Leigh; Runyon, Michael; Khadpe, Jay; Garg, Manish; Cooney, Robert; Hopson, Laura; Pillow, Tyson; Kegg, Jason; Bond, Michael C.; Pearson, David (My University, 2015)
Introduction Clinicians and residency programs are increasing their use of social media (SM) websites for educational and promotional uses, yet little is known about the use of these sites by residents and faculty. The objective of the study is to assess patterns of SM use for personal and professional purposes among emergency medicine (EM) residents and faculty. Methods In this multi-site study, an 18-question survey was sent by e-mail to the residents and faculty in 14 EM programs and to the Council of Emergency Medicine Residency Directors (CORD) listserv via the online tool SurveyMonkey™. We compiled descriptive statistics, including assessment with the chi-square test or Fisher’s exact test. StatsDirect software (v 2.8.0, StatsDirect, Cheshire, UK) was used for all analyses. Results We received 1,314 responses: 63% of respondents were male, 40% were <30 years of age, 39% were between the ages 31 and 40, and 21% were older than 40. The study group consisted of 772 residents and 542 faculty members (15% were program directors, 21% were assistant or associate PDs, 45% were core faculty, and 19% held other faculty positions. Forty-four percent of respondents completed residency more than 10 years ago. Residents used SM markedly more than faculty for social interactions with family and friends (83% vs 65% [p<0.0001]), entertainment (61% vs 47% [p<0.0001]), and videos (42% vs 23% [p=0.0006]). Residents used Facebook™ and YouTube™ more often than faculty (86% vs 67% [p<0.001]; 53% vs 46% [p=0.01]), whereas residents used Twitter™ (19% vs 26% [p=0.005]) and LinkedIn™ (15% vs 32% [p<0.0001]) less than faculty. Overall, residents used SM sites more than faculty, notably in daily use (30% vs 24% [p<0.001]). For professional use, residents were most interested in its use for open positions/hiring (30% vs 18% [p<0.0001]) and videos (33% vs 26% [p=0.005]) and less interested than faculty with award postings (22% vs 33% [p<0.0001]) or publications (30% vs 38% [p=0.0007]). Conclusion EM residents and faculty have different patterns and interests in the personal and professional uses of social media. Awareness of these utilization patterns could benefit future educational endeavors.